Healthcare policy by other means: Cancer clinical research as "oncopolicy". (January 2022) - Cambrosio, Alberto; Campbell, Jonah; Keating, Peter; Polk, Jessica B.; Aguilar-Mahecha, Adriana; Basik, Mark
Abstract: Social studies of biomedicine often focus on how exogenous policies shape the medical domain. While policy agendas no doubt affect complex biomedical projects, in the present paper we analyze a different dynamic, namely how oncologists enact policy as part of several flagship precision oncology endeavors. Empirically, the article focuses on the U.S. TAPUR trial, the Dutch DRUP trial, and the Canadian CAPTUR trial, which have recently been joined by similar Scandinavian studies. Taken together, these trials represent innovative forms of clinical research that, beyond their varying experimental nature, have been designed to transform the evidential processes to provide access to biomarker-driven treatments. Along with gathering evidence on effectiveness of off-label targeted therapies, their explicit goals include the recentering of a major professional organization around research, and the reframing of healthcare as a learning system seamlessly connecting epistemic, organizational, and economic issues. Accordingly, we analyze the design and implementation of these trials as a form of (onco)policy by other means. Highlights: New clinical trial designs and platforms perform policy by other means. Off-label drugs constitute an experimental space for organizing precision oncology. Off-label drug testing extends the experimentality of approved therapies. Beyond the clinic, new trials reshape higher-level organizational arrangements.